Use of the Physician Orders for Life-Sustaining Treatment Program for Patients Being Discharged from the Hospital to the Nursing Facility - Hickman, Susan E. (Mary Ann Liebert, Inc., 2014)
Background: The Physician Orders for Life-Sustaining Treatment (POLST) documents patient preferences as medical orders that transfer across settings with patients. Objectives: The objectives were to pilot test methods and gather preliminary data about POLST including (1) use at time of hospital discharge, (2) transfers across settings, and (3) consistency with prior decisions. Study Design: Descriptive with chart abstraction and interviews. Participants: Participants were hospitalized patients discharged to a nursing facility and/or their surrogates in La Crosse County, Wisconsin. Measurements: POLST forms were abstracted from hospital records for 151 patients. Hospital and nursing facility chart data were abstracted and interviews were conducted with an additional 39 patients/surrogates. Results: Overall, 176 patients had valid POLST forms at the time of discharge from the hospital, and many (38.6%; 68/176) only documented code status. When the whole POLST was completed, orders were more often marked as based on a discussion with the patient and/or surrogate than when the form was used just for code status (95.1% versus 13.8%, p<.001). In the follow-up and interview sample, a majority (90.6%; 29/32) of POLST forms written in the hospital were unchanged up to three weeks after nursing facility admission. Most (71.9%; 23/32) appeared consistent with patient or surrogate recall of prior treatment decisions. Conclusion: POLST forms generated in the hospital do transfer with patients across settings, but are often used only to document code status. POLST orders appeared largely consistent with prior treatment decisions. Further research is needed to assess the quality of POLST decisions.